Oligoryzomys flavescens (Rodentia, Muridae): gene flow among populations from central-eastern Argentina - Chiappero, Marina B (1997)
Fil: Chiappero, Marina B. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Cátedra de Química Biológica; Argentina.